Systematics, DNA barcoding and conservation of Vanilla species from Peninsular Malaysia - Mohd Raffi, Mohd Akmal (2018)
Among the 25 000 orchid species in Orchidaceae family, Vanilla is the most appreciated as it is the only genus with species of high commercial agriculture value for its vanillin production. The species from Peninsular Malaysia which represents the secondary gene pool of the cultivated Vanilla planifolia serves as valuable resources for genetic improvement in Vanilla. However, the potential of each species still remain in secrecy as the genus is not comprehensively studied yet. This study was conducted to assess the native species through systematics and molecular investigations. The data obtained will be used in their conservation management. Therefore, efforts in locating, collecting and documenting local Vanilla were initiated. The field samplings were conducted from 2011 to 2017 in the states of Kedah, Perak, Pahang, Kelantan, Terengganu, Selangor, Negeri Sembilan and Johor. In general, wild Vanilla populations in Peninsular Malaysia were difficult to locate because they were found in many habitats. The diversity in the genus was updated with the discovery of two new species to science, Vanilla norashikiniana R. Go et A. Raffi and Vanilla sanguineovenosa R. Go et A. Raffi which made up the total count from this region to be represented by seven confirmed species. Vanilla spp. most likely could tolerate the cardinal temperature of 17 to 27 oC, relative humidity of 72 to 92% and 64 mm to 733 mm of monthly precipitation. Five important growth events and their interactions with different environmental cues were presented with the emphasized on the flowering stages. The fluctuations of temperature and high light intensity were seen as the natural flowering promoters. Anthesis in Vanilla spp. were ideal to be categorized into five important phases: floral evocation, floral bud emergence, ovary development, size increment in bud and ovary and anthesis. Ephemeral flowering sequences of both newly described taxa were photographed where the anthesis and senescence processes were completed within 24 hours. Investigations at the histological level on accessions from Perak revealed the taxonomic value of the marginal outlines from leaf transverse sections. Somatic chromosome counts (2n) among selected accessions including two new species were found to be different in their most frequent number but shared a common denominator of 2n= 24. Species discrimination inferred by the phylogenetic trees generated from nuclear ribosomal internal transcribed spacer (nrITS) region had classified the accessions into their respective genotypes with two unidentified genotypes suggesting presence of additional species in this region. Barcoding gap was also reported in genetic distance analysis with the speciation threshold recommended to be at 1.5% divergence. Finally, provisional conservation action plan was proposed based on the identified threats of which natural disasters and over collection from the wild were noted as the major threats. Five approaches were evaluated to be pragmatic and should be incorporated in the genus conservation action plan which were species mapping based on the documented localities, local community involvement of Orang Asli, propagation via stem cuttings using BAP, DNA barcodes deposition in BOLD and GenBank and also public education via MyBIS. This project as a whole has successfully documented important findings in the botany and natural history of the genus Vanilla from Peninsular Malaysia and these data are beneficial to the species strategic management planning.